PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, PENGETAHUAN PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA KPP PRATAMA SERPONG) - Jelita, Yosefina Osilia; Finatariani, Endah (Publika Citra Media, 2024)
This research aims to determine the influence of the use of information technology, tax knowledge and taxpayer awareness on individual taxpayer compliance. This type of research is quantitative research. The method used in collecting primary data is by distributing questionnaires to taxpayers. The population of this research is Taxpayers registered at KPP Pratama Serpong. The sampling technique was carried out using the incidental sampling method and obtained 100 respondent data as a result of distributing the questionnaire. The analytical method used in this research is descriptive statistical test analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing using SPSS 23 software. The results of the research using the t or partial statistical test show that the use of Information Technology, Tax Knowledge and Taxpayer Awareness influence Individual Taxpayer Compliance